Media and Culture: The role of media and social media in the formation and dissemination of popular, local, global and international culture - Dahlan, Nur Fadillah (Journal of Studies on Art, Culture and Society, 2024)
This article discusses the role of mass media and social media in forming and disseminating popular culture at local, global and international levels. Mass media and social media significantly influence people's values, norms and lifestyles. Mass media and social media can reinforce, create or change existing culture in a society. Popular culture appeals to many people and is influenced by the entertainment industry. Local culture is a culture that develops in a specific region and has its characteristics. Global culture is a culture that spreads throughout the world and is universal. International culture is a culture that crosses national borders and is multicultural. This article also discusses the positive and negative effects of mass media and social media on society's culture.